Senegal : First Review Under the Policy Support Instrument; Staff Report; Staff Supplement; Press Release; and Statement by the Executive Director for Senegal. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Senegal's economic recovery is continuing and has been largely unaffected by the political crisis in Cote d'Ivoire. Policy discussions focused on the economic implications of two new developments since the program was approved in December 2010. Fiscal policy faces a difficult trade-off between additional priority expenditure and the need to preserve debt sustainability. The sustainability of Senegal's external public and publicly guaranteed (PPG) debt appears vulnerable to rollover risks. This highlights the need for prudent debt management by Senegal, as it seeks to gain greater access to external resources.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet